FACTORS CONTRIBUTING TO THE EMERGENCE OF OBJECTS IN THE TRADITIONS OF CATTLE-HERDING COMMUNITIES IN THE SOPOLLΙ CULTURE (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article examines the factors contributing to the emergence of pottery, metal objects, and burial forms characteristic of the Eurasian steppe nomadic tradition in the material culture of farming communities in Southern Uzbekistan during the Bronze Age.